Applications of Polydopamine-Modified Scaffolds in the Peripheral Nerve Tissue Engineering - Yan, Ji; Wu, Ruoyin; Liao, Sisi; Jiang, Miao; Qian, Yun (Frontiers in Bioengineering and Biotechnology, 2020)
Peripheral nerve injury is a common and complicated traumatic disease in clinical neurosurgery. With the rapid advancement and development of medical technologies, novel tissue engineering provides alternative therapies such as nerve conduit transplantation. It has achieved significant outcomes. The scaffold surface modification is vital to the reconstruction of a pro-healing interface. Polydopamine has high chemical activity, adhesion, hydrophilicity, hydroscopicity, stability, biocompatibility and other properties. It is often used in the surface modification of biomaterials, especially in the peripheral nerve regeneration. In this review, we introduce the hypothesis that polydopamine can promote the adhesion, proliferation and differentiation of neural stem cells and the growth of neuronal processes. Polydopamine was preliminarily used in the surface modification of nerve conduits and had a potential application prospect of the repair of peripheral nerve injury. Polydopamine modified scaffolds are promising in the peripheral nerve tissue engineering.